Paclitaxel as Albumin-Bound Nanoparticles with Gemcitabine for Untreated Metastatic Pancreatic Cancer: An Evidence Review Group Perspective of a NICE Single Technology Appraisal - Stainthorpe, Angela (Pharmacoeconomics, 2018)
As part of the single technology appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited Celgene Ltd to submit clinical and cost-effectiveness evidence for paclitaxel as albumin-bound nanoparticles (Nab-Pac) in combination with gemcitabine (Nab-Pac + Gem) for patients with untreated metastatic pancreatic cancer. The STA was a review of NICE’s 2015 guidance (TA360) in which Nab-Pac + Gem was not recommended for patients with untreated metastatic pancreatic cancer. The review was prompted by a proposed Patient Access Scheme (PAS) discount on the price of Nab-Pac and new evidence that might lead to a change in the guidance. The Liverpool Reviews and Implementation Group at the University of Liverpool was the Evidence Review Group (ERG). This article summarises the ERG’s review of the company’s evidence submission for Nab-Pac + Gem, and the Appraisal Committee (AC) decision. The final scope issued by NICE listed three comparators: gemcitabine monotherapy (Gem), gemcitabine in combination with capecitabine (Gem + Cap), and a combination of oxaliplatin, irinotecan, leucovorin and fluorouracil (FOLFIRINOX). Clinical evidence for the comparison of Nab-Pac + Gem versus Gem was from the phase III CA046 randomized controlled trial. Analysis of progression-free survival (PFS) and overall survival (OS) showed statistically significant improvement for patients treated with Nab-Pac + Gem versus Gem. Clinical evidence for the comparison of Nab-Pac + Gem versus FOLFIRINOX and versus Gem + Cap was derived from a network meta-analysis (NMA). Results of the NMA did not indicate a statistically significant difference in OS or PFS for the comparison of Nab-Pac + Gem versus either Gem + Cap or FOLFIRINOX. The ERG’s main concerns with the clinical effectiveness evidence were difficulties in identifying the patient population for whom treatment with Nab-Pac + Gem is most appropriate, and violation of the proportional hazards (PH) assumption in the CA046 trial. The ERG highlighted methodological issues in the cost-effectiveness analysis pertaining to the modelling of survival outcomes, estimation of drug costs and double counting of adverse-event disutilities. The AC accepted all the ERG’s amendments to the company’s cost-effectiveness model; however, these did not make important differences to the incremental cost-effectiveness ratios (ICERs). The company’s base-case ICER was £46,932 per quality-adjusted life-year (QALY) gained for the comparison of Nab-Pac + Gem versus Gem. Treatment with Nab-Pac + Gem was dominated both by treatment with Gem + Cap and with FOLFIRINOX in the company’s base case. The AC concluded that the most plausible ICER for treatment with Nab-Pac + Gem versus Gem was in the range of £41,000–£46,000 per QALY gained. The AC concluded that Nab-Pac + Gem was not cost effective compared with Gem + Cap or FOLFIRINOX, and accepted that treatment with Nab-Pac + Gem met the end-of-life criteria versus Gem but did not consider Nab-Pac + Gem to meet the end-of-life criteria compared with Gem + Cap or FOLFIRINOX. The AC also concluded that although patients who would receive Nab-Pac + Gem rather than FOLFIRINOX or Gem + Cap were difficult to distinguish, they were identifiable in clinical practice. The AC recommended treatment with Nab-Pac + Gem for patients with untreated metastatic pancreatic cancer for whom other combination chemotherapies were unsuitable and who would otherwise receive Gem.